Sumber Daya Manusia dan Pengelolaan Lahan Pertanian di Pedesaan Indonesia (Forum Penelitian Agro Ekonomi, 2016)
EnglishAgricultural development during the last three decades was able to stimulate the growth of agricultural produciton, and decrease the number of poor people in rural areas. The benefits accured from the development however, were still unevenly distributed, especially when taking account on farmers' family welfare, which was still far from what has formerly been expected. Viewed from the aspect of human resource development it can be showen that labour productivity in the agricultural sector was still far behind those in the other sectors, and this was mainly due to the large portion of labour concentrated in agriculture, resulting in an average contribution of labour in agriculture of 26 hours per week per labourer, compared with those of the other sectors which is 44 hours per week per labourer. One cause of this was the bimodal or dual policy in economy, applied in agricultural development in Indonesia, which is noncundicive for developing a sector with surplus of labourer like agriculture. A strategy of unimodal agricultural development, giving priority to small scale family operated farmlands by providing access to arable lands, technology and financial resources, is therefore considered a proper strategy to be implemented in the future. For implementing this policy, support from macro-economic policy through establishment of proper exchange value and interest rate in accordance with market mechanism accompanied by a balanced and fair fiscal policy should be recommended. IndonesianPembangunan pertanian selama tiga dasa warsa yang lalu telah berhasil memacu pertumbuhan produksi pertanian dan mengurangi jumlah penduduk miskin di pedesaan. Walaupun demikian ditinjau dari aspek pemerataan pemanfaatan hasil pembangunan apalagi terkait dengan kesejahteraan petani, maka dapat dikatakan bahwa apa yang dicapai masih jauh dari yang diharapkan. Dari aspek pengembangan sumber daya manusia, produktivitas tenaga kerja pertanian masih jauh di bandingkan sektor lainnya, dan ini terutama disebabkan masih besarnya porsi tenaga kerja yang bekerja di pertanian, sehingga rata-rata partisipasi tenaga kerja pertanian hanya 26 jam per minggu, jauh dibawah sektor lainnya yang telah mencapai 44jam per minggu. Salah satu penyebab dari kenyataan diatas akibat diterapkannya kebijakan Bimodal atau dual economy dalam pembangunan pertanian di Indonesia, yang kurang kondusif bagi sektor yang surplus tenaga kerja seperti pertanian. Strategi pembangunan pertanian Unimodal dengan memberikan prioritas pada pengembangan pertanian keluarga skala kecil dan meningkatkan akses mereka terhadap lahan, teknologi dan sumber pembiayaan merupakan salah satu strategi yang tepat untuk di lakukan pada masa yang akan datang. Agar kebijaksanaan ini dapat terlaksana dibutuhkan dukungan kebijaksanaan Ekonomi makro melalui kebijakan nilai tukar dan tingkat suku bunga yang mengikuti mekanisme pasar serta kebijaksanaan fiskal yang berimbang dan adil.